TINJAUAN YURIDIS PEMERASAN SEKSUAL (SEXTORTION) DALAM UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASAN SEKSUAL - Rischa Puspita Sari; Davit Rahmadan; Tengku Arif Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The development of information and technology has given rise to virtualsexual activity called sextortion. In Indonesia, various existing regulations havenot been able to become a legal basis to properly protect victims of sextortioncrimes. In fact, sextortion cases are one of the most widespread forms of onlinesexual violence in Indonesia. The purpose of writing this thesis is: First, to findanswers regarding the concept of sexual extortion (sextortion) in positive law inIndonesia. The second is to find a solution to the problem regarding the preciseboundaries regarding sexual extortion (sextortion) in Law Number 12 of 2022concerning Crimes of Sexual Violence.This research uses normative juridical methods. The author conductedresearch on doctrines or principles in legal science, especially on the principle oflegal certainty, which is descriptive in nature. In this research, the data sourceused is secondary data source. Data collection was carried out by means oflibrary research, with qualitative data analysis.The results of the research in writing this thesis can be concluded. Firstly,the concept of sexual blackmail (sextortion) in positive law in Indonesia isregulated in the Criminal Code, the Pornography Law, the ITE Law and theTPKS Law, however the existing regulations still have weaknesses in providingprotection to victims. Second, regarding sextortion crimes in Indonesia in LawNumber 12 of 2022 concerning Crimes of Sexual Violence, there are stillweaknesses in terms of the definition of sextortion, the threat of blackmail used insextortion crimes, information or electronic documents used in sextortion crimes,and how to obtain them. Thus, there is still a need to refine and explain theelements of the articles in the sextortion act in order to fill legal gaps and providelegal certainty in future sextortion cases.Keywords : Criminal Act – Sexual Violence – Sextortion